A new species of Velia (Hemiptera: Heteroptera: Veliidae) from West Bengal, India - Basu, Srimoyee; Subramanian, K. A.; Polhemus, Dan A. (Zootaxa, 2013)
A new Oriental species of water crickets, Velia (Cesavelia) mitrai sp. nov. is described from the vicinity of Darjeeling, West Bengal, India. It was collected from a shaded stream with slow current, situated at an altitude of 2006 m a.s.l. within the Neora Valley National Park. This species is the fourth member of this genus known from India.